A Third-Order Item Response Theory Model for Modeling the Effects of Domains and Subdomains in Large-Scale Educational Assessment Surveys. (August 2014) - Rijmen, Frank; Jeon, Minjeong; von Davier, Matthias; Rabe-Hesketh, Sophia
Second-order item response theory models have been used for assessments consisting of several domains, such as content areas. We extend the second-order model to a third-order model for assessments that include subdomains nested in domains. Using a graphical model framework, it is shown how the model does not suffer from the curse of multidimensionality. We apply unidimensional, second-order, and third-order item response models to the 2007 Trends in International Mathematics and Science Study. Our findings suggest that deviations from unidimensionality are more pronounced at the content domain level than at the cognitive domain level and that deviations from unidimensionality at the content domain level become negligible after taking into account topic areas.